1974
DOI: 10.1111/j.1432-1033.1974.tb03894.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Formate‐Lyase of Escherichia coli: the Acetyl‐Enzyme Intermediate

Abstract: The reaction pyruvate + CoA % acetyl-CoA + formate, catalyzed by pyruvate formate-lyase of Escherichia coli, occurs by the succeeding half-reactions (a) E + pyruvate e E-acetyl + formate; (b) E-acetyl + CoA Making use of coupled optical assays, a 'ping-pong mechanism' was derived from the complete kinetic investigation of the forward and reverse reactions. The thermodynamic equilibrium constant of the overall reaction was calculated from the kinetic constants to be K = 750 (30 "C, pH 8.1), which agrees with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
1
3

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 18 publications
6
162
1
3
Order By: Relevance
“…PFL activity was measured by using a modification of the coupled enzymatic assay previously described [7]. The coupling assay mix contained 150 mM Tris-Cl pH 8.5, 3 mM NAD + , 55 μM CoA, 0.1 mg BSA, 10 mM pyruvate, 10 mM malate, 6 units citrate synthase, and 14 units malic dehydrogenase in a total volume of 700 μL.…”
Section: Pfl Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…PFL activity was measured by using a modification of the coupled enzymatic assay previously described [7]. The coupling assay mix contained 150 mM Tris-Cl pH 8.5, 3 mM NAD + , 55 μM CoA, 0.1 mg BSA, 10 mM pyruvate, 10 mM malate, 6 units citrate synthase, and 14 units malic dehydrogenase in a total volume of 700 μL.…”
Section: Pfl Activity Assaymentioning
confidence: 99%
“…In addition to this transcriptional regulation, PFL requires post-translational activation by the pyruvate formate-lyase activating enzyme (PFL-AE) [5]. PFL-AE is constitutively expressed under both aerobic and anaerobic conditions [6], however in vitro studies have demonstrated that it is catalytically active only under anaerobic reducing conditions [7,8]. There are, therefore, at least two levels of control for regulating PFL activity: transcriptional up-regulation and post-translational activation.…”
Section: Introductionmentioning
confidence: 99%
“…(16)) and pyruvate formate lyase (PFL) (Eq. (17)) are taken from [19] and [20], respectively. Synthesis of succinate (SucSynthesis) is described by a MichaelisMenten equation (Eq.…”
Section: Mathematical Model Of E Coli Metabolismmentioning
confidence: 99%
“…Equation (20) imposes that an increase in certain enzyme level is compensated by a decrease in the activity of the remaining enzymes in order to keep the total enzyme activity [22,23]. To account for changes in all enzymes when only L (L<M) are modulated; Eq.…”
Section: Optimization Model Descriptionmentioning
confidence: 99%
“…Pyruvate formate-lyase (PFL; EC 2.3.1.54) is a key enzyme in fermentative growth and is responsible for converting pyruvate to acetyl coenzyme A and formate, which serve as substrates for the production of acetate, ethanol, hydrogen gas, and carbon dioxide (14). The activity of PFL is regulated by a reversible enzymatic interconversion of an active form to an inactive form in response to oxygen (6).…”
mentioning
confidence: 99%